In situ synthesis of novel biomass lignin/silica based epoxy resin adhesive from renewable resources at different pHs. Issue 16 (18th August 2019) - Zhu, Yanchao; Di, Bing; Chen, Hongzhuo; Wang, Xiaofeng; Tian, Yumei
Abstract: Novel biomass lignin/silica composites were prepared and isolated from rice husk renewable resources at different pHs. Selective precipitation was achieved by decreasing the solution pH from 9.5 to 1.5. When pH reached 3.5, the ratio of lignin and silica mostly achieved the maximum of 1:1. We selected lignin/silica composites as reactants to replace 20 wt% bisphenol A in preparing epoxy resin. The cured novel biomass function lignin/silica-based epoxy resin adhesive showed the highest adhesive strength up to 2.68 MPa, which displayed 123% of neat epoxy resin adhesive. In addition, lignin/silica composites were depolymerized through the hydrothermal method by NaOH as a catalyst, which was used as reactants to replace 35 wt% bisphenol A in the process of in situ synthesis of epoxy resin adhesive. At this point, the high epoxy value (1.42 wt%) and large adhesive strength (3.98 MPa) of lignin/silica-based epoxy resin adhesive were obtained, which adhesive strength was 183% of neat epoxy resin adhesive. The results demonstrated that depolymerized lignin/silica-based epoxy resin adhesive showed the higher epoxy value and the adhesive strength compared with neat epoxy resin adhesive and lignin/silica-based epoxy resin adhesive. Their function in epoxy matrix resulted in better processability.